Exploring the Role of Green Advertising in Shaping Generation Z’s Purchase Intentions for GESITS Electric Motorbikes: A TPB Perspective in JABODETABEK Area - Hanafiah, Ali; Djabbar, Renaldi Utama (International Journal of Integrative Sciences, 2024)
This study seeks to examine the impact of Green Advertising, utilizing the Theory of Planned Behavior, on the purchasing intentions of Generation Z for GESITS Electric Motorbikes. This research targets Generation Z respondents residing in the JABODETABEK region of Indonesia. The research sample comprised 200 respondents. The sampling approach employed was purposive sampling, and the technology utilized was SEM-PLS with the SmartPLS 4 analytic tool. This research indicates that Attitude, Subjective Norm, Perceived Behavioral Control, and Green Advertising positively and significantly influence Generation Z's Purchase Intention for GESITS electric motorbikes